The 2020 Vision for Food, Agriculture and the Environment in South Asia: a synthesis - Rosegrant, Mark W.; Malik, Sohail (International Food Policy Research Institute, 1995)
As part of its 2020 Vision for Food, Agriculture, and the Environment initiative, IFPRI held workshops in three developing regions of the world. The workshop on South Asia, jointly sponsored by the Institute for Integrated Development Studies of Nepal and IFPRI, was held in Kathmandu, Nepal, 26-29 March 1995. This synthesis is based on discussions among some 19 South Asian researchers, technical experts, and policymakers and 9 IFPRI staff who participated in the workshop, and the objectives and strategies noted below are those agreed upon by the workshop participants.